Evaluación de las actividades de emprendimiento e inserción laboral del Centro del Muchacho Trabajador de la ciudad de Quito. - Gallo Romero, Evelin Alicia (2014)
This research is divided into five chapters, in which the information content that allows the "Assessment of entrepreneurial activities and employment of Working Children in Quito Center" to identify their participation in society unfolds, 2013. It starts with the problem statement, objectives and justification to be the basis for the development of research. Regarding the reference framework elaborates on concepts like: Evaluation, employability and entrepreneurship that are directly related to the subject matter; likewise priority is given to laws and articles of the Constitution of the Republic of Ecuador, the Labour Code and the ILO.